Peripheral intravenous catheter dressing and securement practice is associated with site complications and suboptimal dressing integrity: A secondary analysis of 40, 637 catheters. (December 2019) - Corley, Amanda; Ullman, Amanda J.; Mihala, Gabor; Ray-Barruel, Gillian; Alexandrou, Evan; Rickard, Claire M.
Abstract: Background: With over 2 billion peripheral intravenous catheters used globally each year, avoiding complications is crucial for patients and healthcare organisations. Effective catheter dressing and securement is a key nursing strategy to reduce catheter failure and resultant patient harm. Objectives: To describe global catheter dressing and securement practices and policy; and identify factors associated with catheter insertion site complications, and suboptimal dressing and securement. Design: Secondary analysis of a global cross-sectional study of peripheral intravenous catheter characteristics, management and outcomes. Setting: Four hundred and seven rural, regional and metropolitan hospitals in 51 countries. Participants: Paediatric and adult patients with 40, 637 catheters. Methods: Patient-, catheter-, and institution-related factors which could be associated with catheter site complications and suboptimal dressings were extracted from the parent database. Global trends in catheter dressing and securement policy and practice were described. Potential predictors of catheter and dressing complications were explored using logistic regression. Results: Dressing and securement practices, and local hospital policy regarding dressing change frequency varied. One fifth of dressings (21%, n  = 8519) were not clean, dry and intact. The prevalence of catheter insertion site complications was 16% ( n  = 6503), with signs of phlebitis commonly observed (11.5%, n  = 4587). Compared to non-bordered polyurethane dressings, sterile gauze and tape dressings were associated with fewer insertion site complications (odds ratio 0.58, 95% confidence interval 0.50–0.68) and better dressing integrity (odds ratio 0.68; 95% confidence interval 0.59–0.77); whereas, compared with no securement, non-sterile tape at the insertion site was associated with more site complications (odds ratio 2.39, 95% confidence interval 2.22–2.57) and poorer dressing integrity (odds ratio 1.64, 95% confidence interval 1.51–1.75). Two 'bundled' dressing and securement combinations were associated with fewer site and dressing complications, when compared with the reference category. Local catheter care guidelines which advocate 4th hourly insertion site inspection and dressing replacement between 1–3 days were associated with better catheter dressing integrity. Conclusion: Modifiable risk factors for peripheral intravenous catheter site and dressing complications were identified and are amendable to further interventional testing.